A20 haploinsufficiency caused by loss‐of‐function TNFAIP3 mutation likely leads to progression of antiphospholipid syndrome to marginal zone lymphomas following coronavirus disease 2019 vaccination: A case study. Issue 2 (28th March 2023) - Li, Jie; Fu, Xuekun; Xu, Haichan; Li, Bowen; Nie, Liping; Ji, Ling; Liang, Chao
Abstract: Antiphospholipid syndrome (APS) is a rare autoimmune systemic disorder. Previously, no report suggests that APS could progress to extranodal marginal zone lymphomas (EMZL). In this study, we met an unusual APS patient with such progression to EMZL. The patients had been diagnosed with APS two years ago and was in a stable condition after regular treatment until his readmission to our hospital and re‐diagnosed with EMZL recently. Coincidentally, we noticed that the patient had been immunized against inactivated COVID‐19 vaccine just 2 days before his readmission. Furthermore, we performed whole‐exome sequencing and identified a heterozygous, new variant in TNFAIP3 (tumor necrosis factor, α‐induced protein 3) which encoded A20 protein, a key molecule controlling NF‐κB signaling. This variation caused a loss of a base A in TNFAIP3 gene at position 443_444, leading to a frameshift mutation and the production of a truncated A20 Lys148fs*67. A20 Lys148fs*67 failed to suppress TNF‐α‐induced NF‐κB activation and might act through haploinsufficiency. Vaccines work by triggering an immune response to a virus or bacterium within the body. A20 negatively regulates NF‐κB signaling to protect immune system from overactivation. In our case, the newly identified mutation in the TNFAIP3 led to the production of a loss‐of‐function A20 Lys148fs*67, which lost the ability to inhibit inflammation. The patient with such a heterozygous mutation, when facing with the "second hit" of COVID‐19 vaccination challenge, might produce excessive amounts of inflammatory cytokines and formed "cytokine storm" duo to A20 haploinsufficiency, eventually leading to the progression from APS to EMZL. Abstract : This short communication describes a rare case of an antiphospholipid syndrome patient who progressed to extranodal marginal zone lymphomas following the coronavirus disease 2019 vaccination. The patient carried a novel heterozygous mutation in the TNFAIP3 gene which encoded A20, a key molecule controlling NF‐κB signalling. This variation led to the production of a loss‐of‐function A20 Lys148fs*67, which lost the ability to inhibit inflammation.